A new record of the genus Lepisanthes Blume (Sapindaceae Juss.) for the flora of Vietnam - Tam, Ha Minh; Khoi, Nguyen Khac; Phuong, Vu Xuan (Academia Journal of Biology, 2014)
The genus Lepisanthes Blume (Sapindaceae Juss.) has 24 species distributing in tropical Africa, Madagascar, S and SE Asia from Sri Lanka to Hainan (China), Malesian area and NW Australia. According to Pierre (1895), Lecomte (1912), Gagnepain (1950), Pham Hoang Ho (2000), Tran Kim Lien & Ha Minh Tam (2003)..., in Vietnam, the genus Lepisanthes have 6 species: Lepisanthes amplifolia (Pierre) Leenh., Lepisanthes banaensis Gagnep., Lepisanthes fruticosa (Roxb.) Leenh., Lepisanthes rubiginosa (Roxb.) Leenh., Lepisanthes senegalensis (Poir.) Leenh. and Lepisanthes tetraphylla (Vahl) Radlk. During the study of the specimen Vu Dung 36 collected in Gialai province (Ankhe), we have identified that it is Lepisanthes unilocularis Leenh., a new record for the flora of Vietnam. The clearest difference between Lepisanthes unilocularis and all other species of the genus Lepisanthes is in ovary and fruit. The ovary and fruit of Lepisanthes unilocularis always has one loculas while the ovary and fruit of other species of the genus Lepisanthes often has 2-3(-4) loculi. In this article, we add some informations of the flower chracteristics for Leenhouts’description.